Masa Depan Pluralisme Agama Sebagai Koeksistensi Umat Beragama Di Indonesia - Mawardi (Asketik: Jurnal Agama dan Perubahan Sosial, 2022)
This paper aims to analyze the future of religious pluralism as religious coexistence in Indonesia, amidst the wave of religious conservatism worldwide. This research uses a library research approach to explore data in building arguments for predicting the coexistence of religious communities in Indonesia. This study found that Islam provides freedom to choose and believe and worship according to their respective beliefs. The choice of a belief is a free personal choice, so the MUI's view regarding the haram of religious pluralism does not represent the views of Muslims in general. And the coexistence of religious people in the view of pluralists is very wide open even in an era that leads to a conservative turn like today. But it could fail to materialize if the truth claim among religious people, especially Muslims, is increasingly crystallized and tends to lead to extreme fanaticism.